Revitalization of Islamic Boarding School Management to Foster the Spirit of Islamic Moderation in Indonesia - Fathurrochman, Irwan; Ristianti, Dina Hajja; Arif, Mohamad Aziz Shah bin Mohamed (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
Islamic moderation-based boarding school management is vital to be carried out amidst the negative stigma of radicalism. This study aims to analyze the management revitalization of Islamic boarding schools conducted by Islamic boarding schools in Bengkulu, Indonesia, i.e., Miftahul Jannah, Hidayatullah, Ar-Rahmah, Muhammadiyah, and Al-Hijaaz Islamic boarding schools, in order to foster a spirit of Islamic moderation in Indonesia. This study used a qualitative method. The researchers were actively involved in managerial activities in Islamic boarding schools as a part of uncovering phenomena that occur in Islamic boarding schools. The results showed that the revitalization of boarding school management in order to have a significant role in preventing radicalism was done by creating commitment and not giving the slightest opportunity to the emergence of radicalism, returning the position of the existence of boarding schools as tafaqquh fiddin and boarding school managers committed to not engage in practical politics, to monitor strictly all boarding school programs to be free from radicalism. The spirit of Islamic moderation is used as a foothold in the practice of religious life so that Islamic boarding schools become a driving force in fostering the spirit of Islamic moderation.